PEMANFAATAN LIMBAH BUAH-BUAHAN SEBAGAI EKOENZYME DAN PUPUK KANDANG SAPI UNTUK PERTUMBUHAN TANAMAN SELADA HIJAU (LACTUCA SATIVA L.) - Panjaitan, Delima; sulastri, yustina sri (AGROSUSTAIN, 2023)
This research aims to determine the effect of providing eco-enzymes and cow manure on the growth of lettuce plants. This research was carried out in Bandar Baru Village, Sibolangit District, Deli Serdang Regency and was carried out from July to September 2023. This research used a factorial Randomized Group Design (RAK) consisting of 2 factors. The first factor in giving cow manure (P) consists of 4 levels, namely P0: 0 tons/ha (0 g/bed), P1: 10 tons/ha (126 g/bed), P2: 20 tons/ha (251 g/bed). bed), P3: 30 tons/ha (377 g/bed) and the second factor of ecoenzyme (K) consists of 3 levels, namely K0: 0 ml/plant, K1: 6 ml/plant, K2: 8 ml/plant , and K3: 10 ml/plant. Data analysis uses analysis of variance. The research results showed that cow manure had a real influence on plant height, number of leaves, net root weight, plot wet weight and plot dry weight. The highest plants were obtained at a dose of 251 gr. Ecoenzyme had a significant effect on net root weight, plot wet weight, and plot dry weight. The interaction between giving cow manure and giving eco-enzymes had no effect on the parameters of plant height, number of leaves, net root weight, plot wet weight, plot dry weight.